Dynamic atlas of immune cells reveals multiple functional features of macrophages associated with progression of pulmonary fibrosis - Lv, Jiaoyan; Gao, Haoxiang; Ma, Jie; Liu, Jiachen; Tian, Yujie; Yang, Chunyuan; Li, Mansheng; Zhao, Yue; Li, Zhimin; Zhang, Xuegong; Zhu, Yunping; Zhang, Jianhong; et al. (Frontiers in Immunology, 2023)
Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease with a high mortality rate and unclarified aetiology. Immune response is elaborately regulated during the progression of IPF, but immune cells subsets are complicated which has not been detailed described during IPF progression. Therefore, in the current study, we sought to investigate the role of immune regulation by elaborately characterize the heterogeneous of immune cells during the progression of IPF. To this end, we performed single-cell profiling of lung immune cells isolated from four stages of bleomycin-induced pulmonary fibrosis—a classical mouse model that mimics human IPF. The results revealed distinct components of immune cells in different phases of pulmonary fibrosis and close communication between macrophages and other immune cells along with pulmonary fibrosis progression. Enriched signals of SPP1, CCL5 and CXCL2 were found between macrophages and other immune cells. We conducted a more detailed definition of the subpopulations of macrophages. Alveolar macrophages (AMs) and monocyte-derived macrophages (mo-Macs)—the two major types of primary lung macrophages—exhibited the highest heterogeneity and dynamic changes in expression of profibrotic genes during disease progression. Our analysis suggested that Gpnmb and Trem2 were both upregulated in macrophages and may play important roles in pulmonary fibrosis progression. Additionally, the metabolic status of AMs and mo-Macs varied with disease progression. In line with the published data on human IPF, macrophages in the mouse model shared some features regarding gene expression and metabolic status with that of macrophages in IPF patients. Our study provides new insights into the pathological features of profibrotic macrophages in the lung that will facilitate the identification of new targets for disease intervention and treatment of IPF.